2017
DOI: 10.1016/j.cognition.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

When categorization-based stranger avoidance explains the uncanny valley: A comment on MacDorman and Chattopadhyay (2016)

Abstract: Artificial objects often subjectively look eerie when their appearance to some extent resembles a human, which is known as the uncanny valley phenomenon. From a cognitive psychology perspective, several explanations of the phenomenon have been put forth, two of which are object categorization and realism inconsistency. Recently, MacDorman and Chattopadhyay (2016) reported experimental data as evidence in support of the latter. In our estimation, however, their results are still consistent with categorization-b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 15 publications
2
21
0
Order By: Relevance
“…Importantly, Yamada et al (2012) showed that individual differences in food neophobia (which leads to trait avoidance of novel foods) predict the degree to which hard-to-categorize objects are perceived negatively. In line with these studies, the categorization-difficulty hypothesis assumed a two-stage process (for more detailed discussions: Kawabe et al, 2017 ). In the first stage, if the appearance of the hard-to-categorize objects is improbable, then observers cannot categorize such objects into already acquired classes of objects but categorize them into a novel class.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Importantly, Yamada et al (2012) showed that individual differences in food neophobia (which leads to trait avoidance of novel foods) predict the degree to which hard-to-categorize objects are perceived negatively. In line with these studies, the categorization-difficulty hypothesis assumed a two-stage process (for more detailed discussions: Kawabe et al, 2017 ). In the first stage, if the appearance of the hard-to-categorize objects is improbable, then observers cannot categorize such objects into already acquired classes of objects but categorize them into a novel class.…”
Section: Introductionmentioning
confidence: 85%
“…These studies suggest that high BIS scorers are sensitive and respond negatively to potential threats. If the hypothesis that the uncanny valley partly results from avoiding strangers ( Yamada et al, 2012 , 2013 , 2014 ; Kawabe et al, 2017 ) is true, then individuals with high BIS scores should feel a strong sense of eeriness from hard-to-categorize objects. On the other hand, the effect of BIS would not appear with easy-to-categorize objects because the category of these objects is obvious, and thus these objects are not novel and seen as potential threats.…”
Section: Introductionmentioning
confidence: 99%
“…In the behavioral immune system ( Park, Schaller, & Crandall, 2007 ; Schaller, 2011 ; Schaller & Park, 2011 ), perceptual cues of infectious pathogens elicit aversive emotions, and, in turn, these emotions facilitate behavioral avoidance. Likewise, the concept of stranger avoidance ( Kawabe et al, 2017 ; Yamada et al, 2012 , 2013 , 2014 ) supposes that when objects are apparently uncertain and difficult to categorize into already acquired classes, we judge the objects as potentially harmful ones to be avoided. Consequently, negative reactions are elicited.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, some situations (such as a dirty toilet), animals (such as spiders and birds), or wounded people can induce strong negative emotions ( Caseras et al, 2007 ; Curtis, Aunger, & Rabie, 2004 ; Sawchuk, Lohr, Westendorf, Meunier, & Tolin, 2002 ). Humans also respond negatively to objects that are difficult to categorize ( Kawabe, Sasaki, Ihaya, & Yamada, 2017 ; Yamada, Kawabe, & Ihaya, 2012 , 2013 ; Yamada, Sasaki, Kunieda, & Wada, 2014 ). These observations suggest the existence of a system to avoid things that may be perceived as unpleasant.…”
Section: Introductionmentioning
confidence: 99%
“…Stimuli whose truncated range precludes observing the Uncanny Valley itself may also disrupt assessment of category confusion in the Uncanny Valley. Second, most studies have generated stimuli through digital image morphing, a method that risks producing unrealistic transitional images exhibiting, for example, partially transparent facial features or incompatible combinations of features that would be avoided in real-world robot design (Kätsyri et al, 2015;Kawabe, Sasaki, Ihaya, & Yamada, 2017). It is plausible that these unrealistic features themselves, rather than the stimuli's degree of human-likeness, might produce artifactual confusion or aversion.…”
Section: Introductionmentioning
confidence: 99%